Advertising - McArthur-Christie, Mark (Oxford, New York Oxford University Press, 2002)
Provides a collection of non-fiction texts, with artwork and cross-curricular links. This series is structured by year, and provides the text types you need for the Literacy Hour. It covers NLS range requirements and objectives at KS2, makes guided reading easy with cards for every book, and makes shared reading simple with double-sided posters.
Include Index, Glossary and Colour Illustration
Keywords: Advertising